2021
DOI: 10.3390/ijms22147252
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of a β-Adrenergic-Like Octopamine Receptor Affects Locomotion and Reproduction of Tribolium castaneum

Abstract: The neurohormone octopamine regulates many crucial physiological processes in insects and exerts its activity via typical G-protein coupled receptors. The roles of octopamine receptors in regulating behavior and physiology in Coleoptera (beetles) need better understanding. We used the red flour beetle, Tribolium castaneum, as a model species to study the contribution of the octopamine receptor to behavior and physiology. We cloned the cDNA of a β-adrenergic-like octopamine receptor (TcOctβ2R). This was heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…The second phenylalanine after the FxxxWxP motif in TM6 and that after the NPxxY motif in TM7 were also conserved. These conserved cysteine and phenylalanine sites are not only necessary for aminergic GPCRs but are also conserved in all previously reported adrenergic receptors [ 29 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The second phenylalanine after the FxxxWxP motif in TM6 and that after the NPxxY motif in TM7 were also conserved. These conserved cysteine and phenylalanine sites are not only necessary for aminergic GPCRs but are also conserved in all previously reported adrenergic receptors [ 29 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 73%
“…However, TcOctβ3 has been found to be highly expressed in early larvae, and there may be differences in the level of expression of this gene among different species. In addition, we found that the level of expression of PxOctβ3 differed in females and males, which was also reflected in PxOctβ1 and PxOctβ2 [ 28 , 29 , 30 ]. In addition, this study confirmed that an increase in the nerve impulse responses of male pheromone-sensitive receptor neurons (RNs) after octopamine injection in silkworm ( Bombyx mori ) is either absent or less sensitive in females [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CcOctβRs were all expressed in the leg. The transcript levels of NcOctβ2R [ 70 ] and TcOctβ2R [ 50 ] were found to exhibit high expressions in the leg. There are large muscles in insect legs, and the expressions of DmOctβRs were all detected in the adult muscles [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The β-adrenergic-like OAR family generally has three subtypes, including Octβ1R, Octβ2R, and Octβ3R. Octβ1R regulates feeding and learning behavior [ 23 , 44 ], and Octβ3R plays an essential role in metamorphosis regulation of ecdysone synthesis and pupation [ 45 , 46 ], whereas Octβ2R has multiple functions, including ovulation [ 47 , 48 , 49 ], locomotion [ 50 , 51 , 52 ], and stress resistance [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that octopaminergic/tyraminergic signalling pathways played essential roles for the insect fertility [33,34]. In invertebrates, octopamine and tyramine might play the roles as epinephrine and norepinephrine played in vertebrates [35].…”
Section: Effect Of Excessive Epinephrine Intake On Mosquito Fecundity...mentioning
confidence: 99%